Improved percent-predicted peak VO2 is associated with lower risk of hospitalization in patients with coronary heart disease. Analysis from the FRIEND registry. (1st July 2020) - Chiaranda, G.; Myers, J.; Arena, R.; Kaminsky, L.; Sassone, B.; Pasanisi, G.; Mandini, S.; Pizzolato, M.; Franchi, M.; Napoli, N.; Guerzoni, F.; Caruso, L.; et al.
Abstract: Background: Normal standards for peak oxygen consumption (VO2 peak) are controversial because they tend to be population and protocol specific. This study was undertaken to examine the association between percentage of age-predicted VO2 peak and all-cause hospital readmission in cardiac outpatients who were referred to an exercise-based secondary prevention program. Methods: Hospital readmission was assessed in 1283 male patients with coronary heart disease (CHD) three years after enrolment, and related to the age-predicted VO2 peak derived from the Fitness Registry and the Importance of Exercise: A National Data Base equation (FRIEND%PRED ). VO2 peak was estimated using a moderate perceptually regulated 1-km treadmill-walking test. Readmission was also assessed during the fourth-to-sixth years as function of improvement in FRIEND%PRED in 845 patients who were re-evaluated 3 years after baseline. Results: During the 3-years after baseline, readmission rate was lower across increasing tertiles of FRIEND%PRED . Compared to the lowest tertile, the adjusted hazard ratios (HRs) for the second and third tertile were 0.98 (95% CI 0.76–1.27, p = 0.90) and 0.71 (0.53–0.95, p = 0.002). The rate of readmission from the fourth-to-sixth years after baseline was lower across tertiles of improved FRIEND%PRED, with adjusted HRs 0.78 (0.60–1.03, p = 0.08) and 0.58 (0.42–0.75, p < 0.0001) for the intermediate and high tertiles vs the lowest tertile. After adjustment for confounders, every 1 unit % increase in FRIEND%PRED was associated with a 3% reduction in risk of readmission (HR 0.97, 0.95–0.98, p < 0.0001). Conclusions: Age-predicted VO2 peak estimated by a moderate treadmill-walk predicts hospital readmission in outpatients with CHD undergoing secondary prevention.